2017
DOI: 10.1016/j.apsusc.2016.10.156
|View full text |Cite
|
Sign up to set email alerts
|

The erosion performance of cold spray deposited metal matrix composite coatings with subsequent friction stir processing

Abstract: This study forms an initial investigation into the development of SprayStir, an innovative processing technique for generating erosion resistant surface layers on a chosen substrate material. Tungsten carbide – cobalt chromium, chromium carbide – nickel chromium and aluminium oxide coatings were successfully cold spray deposited on AA5083 grade aluminium. In order to improve the deposition efficiency of the cold spray process, coatings were co-deposited with powdered AA5083 using a twin powder feed system that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 60 publications
(90 reference statements)
2
47
0
Order By: Relevance
“…1b, a depth-dependent gradient structure is formed on the USSPed Cu coating. Peat et al also reported that a similar gradient structure was obtained in the cold-sprayed WC-CoCr coating by the subsequent friction stir processing [30]. The cross section of the USSPed Cu coating can be divided into three zones: the top-most layer (about 50 μm depth) with dense structure, the intermediate layer (depth ranged from 50 μm to 100 μm) with some pores, and the internal layer with an original pore structure.…”
Section: Effect Of Ussp On Structure and Corrosion Of Pure Cu Coatingmentioning
confidence: 66%
“…1b, a depth-dependent gradient structure is formed on the USSPed Cu coating. Peat et al also reported that a similar gradient structure was obtained in the cold-sprayed WC-CoCr coating by the subsequent friction stir processing [30]. The cross section of the USSPed Cu coating can be divided into three zones: the top-most layer (about 50 μm depth) with dense structure, the intermediate layer (depth ranged from 50 μm to 100 μm) with some pores, and the internal layer with an original pore structure.…”
Section: Effect Of Ussp On Structure and Corrosion Of Pure Cu Coatingmentioning
confidence: 66%
“…Coatings 2020, 10, 123 9 of 35 break up or dissolve the secondary phase particles in the cold sprayed metal matrix composite (MMC) deposits, leading to considerable improvement in mechanical properties. Incorporating cold spray with FSP is a novel two-stage surface engineering process referred to as 'SprayStir' [56,57]. Table 2 summarizes the previous studies regarding the effects of post FSP on cold sprayed coatings.…”
Section: Friction-stir Processing Treatmentmentioning
confidence: 99%
“…[59], with permission from © Elsevier); (b) general morphologies of as-sprayed SiCp/Al5056 coating after FSP at 600 rpm or 1400 rpm (adapted from reference [58],with permission from © Springer Nature); and (c) cross-section view of cold sprayed coating after FSP (adapted from reference [56], with permission from © Elsevier). [59], with permission from © Elsevier); (b) general morphologies of as-sprayed SiCp/Al5056 coating after FSP at 600 rpm or 1400 rpm (adapted from reference [58],with permission from © Springer Nature); and (c) cross-section view of cold sprayed coating after FSP (adapted from reference [56], with permission from © Elsevier). Huang et al [59] studied the grain structures within cold sprayed Cu-Zn alloy coatings before and after FSP via EBSD.…”
Section: Friction-stir Processing Treatmentmentioning
confidence: 99%
“…Even then, the studies employing such concept are limited in the literature and involve successful depositions of W-Cu by Kang and Kang [10] and Deng et al [11], W-Ni-Fe by Xia et al [12], and low tungsten content in W-90Ta coatings by Barnett et al [13] only. Considering their excellent wear properties, a significantly broader series of studies involved the research of cemented carbides in a form of WC-Co [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], WC-Ni [32][33][34][35][36][37][38][39][40][41], WC-Co-Ni [42], WC-Co-Cr [31,[43][44][45], or WC-Cu-MoS 2 [46,47]. Unfortunately, the carbides could not be used for PFCs and so we could not built on these results.…”
Section: Introductionmentioning
confidence: 99%